GRAMMAR PROFICIENCY OF ENGLISH MAJOR STUDENTS USING TIC-TAC-TOE STRATEGY IN PANGASINAN STATE UNIVERSITY, ASINGAN CAMPUS - Terre, Elsa Q. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Grammar is essential to clear communication and can be challenging to teach effectively; however, incorporating interactive games can make the learning process more entertaining and Ceffective. This study is intended to determine the effectiveness of the Tic-Tac-Toe strategy in teaching English grammar and compared it to traditional methods. The researcher employed an explanatory research design to explore why the Tic-Tac-Toe strategy works by providing insights into its impact and guiding future research (George & Merkus, 2023). The participants of the study were the 35 third year English major regular students from Pangasinan State University-Asingan Campus and were divided into two groups: one using the Tic-Tac-Toe strategy with technology aids and the other receiving traditional instruction. A post-test-only design was employed to assess the effectiveness of the two teaching methods. The results showed that the Tic-Tac-Toe strategy greatly outperformed traditional methods in improving grammar skills, though additional reinforcement may be necessary for long-term retention. Furthermore, it is recommended that educators could adopt the Tic-Tac-Toe strategy, integrate it with other innovative methods, explore advanced tools for complex grammar, align programs with students' linguistic backgrounds and implement continuous feedback mechanisms to enhance instructional approaches.